2012
DOI: 10.4028/www.scientific.net/amr.518-523.136
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Factor of Travertine Deposition between Yellowstone National Park (YNP), USA and Huanglong Scenic, Sichuan

Abstract: Yellow Stone National Park (YNP), USA, is well-known as its glorious travertine geomorphology as well as Huanglong National Scenic District in Sichuan, China. But there were some difference between them. The travertine deposition of YNP were formed from geothermal activity, meanwhile Huanglong Scenic District is located in high attitude and cold area and the travertine deposition appeared in the cold water. With the increasing attention to global carbon cycle, origin of life and the life action in the extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Here, a large amount of cold-water travertine was formed with the perennially low temperature (4 °C) and at a high elevation (3145–3578 m). 15 Studies on the travertine in Huanglong have shown that the biodiversity of bacteria and algae is significantly high, and the water contains a large amount of Ca 2+ , Mg 2+ and HCO 3 − , thus forming an unique travertine landform and cold adaption condition. 16 Hence, a study of aboriginal bacteria in Huanglong can provide reference for the research and application of biomineralization in a low temperature environment.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a large amount of cold-water travertine was formed with the perennially low temperature (4 °C) and at a high elevation (3145–3578 m). 15 Studies on the travertine in Huanglong have shown that the biodiversity of bacteria and algae is significantly high, and the water contains a large amount of Ca 2+ , Mg 2+ and HCO 3 − , thus forming an unique travertine landform and cold adaption condition. 16 Hence, a study of aboriginal bacteria in Huanglong can provide reference for the research and application of biomineralization in a low temperature environment.…”
Section: Introductionmentioning
confidence: 99%
“…It turns out that the calcite in Huanglong dams is a typical anisotropic lattice distortion, which means that biogenic factors have contributed to its formation [3]. However, there is little information on how any life form may have contributed to travertine dam formation of Huanglong [4]. Recently, the influence of diatoms on travertine dam formation at the Huanglong Natural Scenic District has been studied but no conclusive information on the direct involvement of diatoms in the direct formation of the calcite structure of the dams has been provided [3].…”
Section: Introductionmentioning
confidence: 99%